Strategies for Maintaining SMEs Performance During Covid-19 Pandemic - Utomo, Mohamad Nur; Ariska, Iin; Pratiwi, Sulistya Rini; Kaujan, Kaujan (International Journal of Social Science and Business, 2021)
The Covid-19 pandemic has forced the world to experience a global economic crisis. Economic decline has greatly harmed the business, including Small and Medium Enterprises (SMEs). Small and Medium Enterprises must be able to take strategic steps to maintain their business. The current research is aimed to conduct empirical test on the effect of responsive digital marketing, customer relationship management, and working capital efficiency on SMEs' efforts to maintain performance during the Covid-19 pandemic. The research sample was 57 respondents who represent SMEs of Processed Food. The data analysis technique used SEM-PLS. Result of research has shown that responsive digital marketing has been proved as helpful to SMEs in maintaining their sale performance during covid-19 pandemic. Besides this result, other finding has shown that main key to maintain customers and sale performance in sustainable manner during covid-19 pandemic is by improving customer satisfaction and building long term relationship with customers. Other finding has indicated that aggressive working capital management will facilitate SMEs to maintain their performance during covid-19 pandemic.